Boron clusters (ferrabisdicarbollides) shaping the future as radiosensitizers for multimodal (chemo/radio/PBFR) therapy of glioblastoma. Issue 47 (14th November 2022) - Nuez-Martínez, Miquel; Queralt-Martín, María; Muñoz-Juan, Amanda; Aguilella, Vicente M.; Laromaine, Anna; Teixidor, Francesc; Viñas, Clara; Pinto, Catarina G.; Pinheiro, Teresa; Guerreiro, Joana F.; Mendes, Filipa; Roma-Rodrigues, Catarina; et al.
Abstract : The cellular damage response induced by γ-rays, X-rays and proton beams suggest these type of radiations are promising therapeutic modalities against resistant glioblastoma tumours when combined to stable metallacarboranes as radiosensitizers and PBFR. Abstract : Glioblastoma multiforme (GBM) is the most common and fatal primary brain tumor, and is highly resistant to conventional radiotherapy and chemotherapy. Therefore, the development of multidrug resistance and tumor recurrence are frequent. Given the poor survival with the current treatments, new therapeutic strategies are urgently needed. Radiotherapy (RT) is a common cancer treatment modality for GBM. However, there is still a need to improve RT efficiency, while reducing the severe side effects. Radiosensitizers can enhance the killing effect on tumor cells with less side effects on healthy tissues. Herein, we present our pioneering study on the highly stable and amphiphilic metallacarboranes, ferrabis(dicarbollides) ([ o -FESAN] − and [8, 8′-I2- o -FESAN] − ), as potential radiosensitizers for GBM radiotherapy. We propose radiation methodologies that utilize secondary radiation emissions from iodine and iron, using ferrabis(dicarbollides) as iodine/iron donors, aiming to achieve a greater therapeutic effect than that of a conventional radiotherapy. As a proof-of-concept, we show that using 2D and 3D models of U87 cells, the cellular viability and survival were reduced using this treatment approach. We also tested for the first time the proton boron fusion reaction (PBFR) with ferrabis(dicarbollides), taking advantage of their high boron ( 11 B) content. The results from the cellular damage response obtained suggest that proton boron fusion radiation therapy, when combined with boron-rich compounds, is a promising modality to fight against resistant tumors. Although these results are encouraging, more developments are needed to further explore ferrabis(dicarbollides) as radiosensitizers towards a positive impact on the therapeutic strategies for GBM.